Validation process of the calcination method for determining the organic matter content in soil samples from Peru (Revista Ciencia Agraria, 2025)
Soil organic matter (SOM) is a key indicator of soil quality due to its impact on physical, chemical, and biological properties. The standardized method in Peru for determining SOM is wet oxidation, which requires the use of controlled chemical reagents; however, their improper disposal poses a risk of environmental contamination. As an alternative, the calcination method can be used, which is less polluting, although the operating temperatures have not yet been standardized nationwide. The aim of this research is to compare the calcination method at three different ignition temperatures with the standardized method. A total of 61 soil samples from various regions of Peru, exhibiting different SOM and CaCO₃ contents, were analyzed. Calcination temperatures were set at 400 °C, 500 °C, and 600 °C. The results compared SOM determined by wet oxidation and SOM determined by calcination using the Wilcoxon test, which showed significant differences (p < 0.05). Linear regression equations were developed to evaluate the correlation between both procedures, and SOM obtained by calcination at the three temperatures showed a strong linear correlation (adjusted R² = 0.88). Among the regression equations for each calcination temperature, the 400 °C treatment exhibited the highest correlation with the standardized method (adjusted R² = 0.92, p < 0.005). These findings suggest that the calcination method at 400 °C can be a useful approach to estimate soil organic matter content across different soil types.
Keywords: correlation; organic matter; wet oxidation; loss on ignition